2013
DOI: 10.1007/s11552-012-9488-z
|View full text |Cite
|
Sign up to set email alerts
|

Wyndell Merritt Immediate Controlled Active Motion (ICAM) Protocol following Extensor Tendon Repairs in Zone IV–VII: Review of Literature, Orthosis Design, and Case Study—A Multimedia Article

Abstract: The Wyndell Merritt ICAM digital yoke orthosis, fabricated with or without wrist immobilization, appears to facilitate the return of normal extensor tendon function after repair in zones IV through VII while minimizing morbidity to adjacent digits. This protocol provides a safe, low-profile, cost-effective alternative for post-operative treatment of zone IV-VII extensor tendon repairs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 5 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Historically IM was the standard procedure following extensor tendon repairs 9 , however with a high risk of complications such as tendon adhesions, joint stiffness 5 , extensor lag and prolonged treatment 12 . As a result, decreased composite flexion occurred 14,15 . In response, both EPM and EAM protocols have been developed to reduce complications related to the IM protocol 13 .…”
Section: Rehabilitation Of Extensor Tendon Repairs From Zone IV To Viimentioning
confidence: 99%
See 2 more Smart Citations
“…Historically IM was the standard procedure following extensor tendon repairs 9 , however with a high risk of complications such as tendon adhesions, joint stiffness 5 , extensor lag and prolonged treatment 12 . As a result, decreased composite flexion occurred 14,15 . In response, both EPM and EAM protocols have been developed to reduce complications related to the IM protocol 13 .…”
Section: Rehabilitation Of Extensor Tendon Repairs From Zone IV To Viimentioning
confidence: 99%
“…In the mid 1980s, post-operative care for repaired extensor tendons in zones IV to VII began to move from IM to controlled EPM by using a dynamic extension splint 15 . While EPM prevents adhesions and preserves flexion, it was found that the bulkiness of the splint interferes with daily function, that it is costly to fabricate and cumbersome to use 15,16 .…”
Section: Rehabilitation Of Extensor Tendon Repairs From Zone IV To Viimentioning
confidence: 99%
See 1 more Smart Citation
“…The RMO uses a thin (1 inch) strip of thermoplastic to keep the injured digit in relative extension at the MCP joint, and minimizes the inherent effect of shortening in all extensor tendon repairs. 40,44,45 …”
Section: Discussionmentioning
confidence: 99%
“…Extensor tendon repairs in zones V and VI can be managed postoperatively by immobilization, controlled passive motion, or through immediate controlled active motion. [19][20][21] Immobilization of the wrist and metacarpophalangeal joints Immobilization following simple zone V and VI extensor tendon repairs has been shown to produce excellent outcomes at 6 months after repair. 22 However, in complex injuries with multiple tendon involvement and/or metacarpal fractures, immobilization produces dense adhesion formation, which limits active and passive tendon glide during both digital flexion and extension.…”
Section: Complicationsmentioning
confidence: 99%